Auditoría de gestión y su relación con el desarrollo administrativo y operacional de la empresa Agripac S.A., cantón Quevedo, período 2012. - De Haz Segovia, Gisella Geomara (2015)
The present study has as it’s theme: “Audit of management and its relation with the development of administrative and operational company AGRIPAC S.A. canton Quevedo, 2012 period”, as it allows a technical way protect the company’s reso urces and provide efficient information. Trough the audit of management seeks to determine its relation with the development of administrative and operationa. The application of the audit in this present research is to analyze their organizational system and compliance with their policies, evaluate the system of internal control, measure indicators of management. This workd is carried out with the collection of interviews and direct observation toprocesses executed in the enity. In what refers to the international control was obtained the following results: on the measurement of risk, risk control, level of trust 87.38% higher, level of risk 12.62% high risk, the measurement of inherente risk level of trust 72% and their inherente risk 28%, therefore the risk of audit is 0.18 indicatinh that it is high. To have audited the company AGRIPAC S.A. was measured their perspective according to the policies and procedures of the same the lack of the internal control at the time for handling of rules to giverecommendations for corrective actions that contribute to the decision-making of the company.